Interference of Compensatory Strategies in Oral Production of English Language Student in an ESL Classroom: Does Compensatory Strategy Play a Role in Academic Performance? - Rubis, Novalyn M.; Dumlao, Remart (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2018)
The study aims to identify the compensatory strategies predominantly used by fifty-four ESL High school student, its relation to language proficiency level in terms of accuracy, fluency, and comprehensibility and to its role in academic performance of the participants. Two oral task namely oral interview and pictured-cued narration were used as primary source of data. The picture-cued narration was applied to determine the oral language proficiency level and compensatory strategies of the participants. Finding shows the eight compensatory strategies were employed in their production, namely, switching to mother tongue, getting help, using mime, selecting the topic, adjusting the message, coining words, avoiding communication partially and totally, and using circumlocution or synonyms. It was also found out that switching to mother tongue was predominantly employed in their oral production. There is, however, negative relationship between compensatory strategies used and academic performance of ESL learners. Pedagogical implications are discussed discussed in the paper. Keywords: communicative competence, compensatory strategies, language classroom, oral production